A deeper dive into the healthy diet basket and global variation in diet costs and affordability - Bai, Yan (2022)
Yan Bai POLICY SEMINAR Are healthy diets affordable? Using new data on retail prices and diet costs to guide agricultural and food policy Co-organized by IFPRI, Tufts University, the World Bank, and Food and Agriculture Organization (FAO) JUL 15, 2022 - 10:00 TO 11:30AM EDT